Synthetic-aperture radar (SAR) processed airborne radio-echo sounding data from the Institute and Moller ice streams, West Antarctica, 2010-11 ... - Siergert, Martin; Corr, Hugh; Ross, Neil; Jordan, Tom; Robinson, Carl; Jeofry, Hafeez; Ferraccioli, Fausto; Bingham, Robert; Le Brocq, Anne; Rippin, David (Polar Data Centre; British Antarctic Survey, Natural Environment Research Council; Cambridge, CB3 0ET, UK., 2017)
SAR-processed two-dimensional radargram data in SEG-Y format acquired from the Institute and Moller ice streams, West Antarctica between mid-December 2010 and mid-January 2011. Data were collected using the British Antarctic Survey (BAS) Polarimetric radar Airborne Science Instrument (PASIN) radar, operated at a centre frequency of 150 MHz, and installed on the BAS Twin Otter aircraft "Bravo Lima". In total, ~25,000km of aerogeophysical data were collected, with coverage extending from the ice stream grounding zone to the ice divide. A high-resolution grid, with a line-spacing of 7.5 x 25 km, was acquired over the central parts of the ice stream catchments. Data were acquired during twenty-eight survey flights (sixteen flown from remote field camp C110, ten from Patriot Hills and two "transit" flights). Funding for this data acquisition was provided by the UK NERC AFI grant NE/G013071/1. ... : Radio-echo sounding (RES) data were acquired over the Institute and Moller ice streams in the Weddell Sea sector of West Antarctica during the Institute-Moller Antarctic Funding Initiative (IMAFI) project from 23rd December 2010 to 9th January 2011. RES data were acquired with the British Antarctic Survey (BAS) Polarimetric radar Airborne Science Instrument (PASIN) radar, using the BAS Twin Otter aircraft "Bravo Lima" as the aerogeophysical platform. The PASIN antenna array is an eight-element folded dipole array attached below the starboard and port wings for reception and transmission. In addition to RES data, the project acquired aerogravity, aeromagnetic, LiDAR, GPS and radar altimeter data. A high-resolution survey grid, with primary line-spacing of 7.5 km, and tielines at 25 km spacing, was acquired over the central part of the ice stream catchments. Additional exploratory aerogeophysical flight lines were acquired to connect the IMAFI survey to existing surveys in adjacent ice streams catchments (e.g. ...